Analysis of Elementary School Teachers’ Knowledge of Scratch Learning Media: Insights from an Islamic Education Perspective - Berlian, Mery; Vebrianto, Rian; Yovita, Yovita; Sahputri, Desi Nori (AT-TA'LIM, 2025)
The rapid advancement of technology has influenced all aspects of human life, including education. In the teaching and learning process, technology plays a crucial role in achieving learning objectives more effectively. Scratch is a simple coding platform that supports the development of students’ computational thinking and creativity. Teachers’ knowledge is essential for the effective implementation of such media. This study aimed to analyze elementary school teachers’ knowledge of Scratch learning media in public and private elementary schools in Pekanbaru, Indonesia. Using a quantitative descriptive survey design, data were collected from 40 classroom teachers across Grades 1 to 6, selected purposively to represent diverse experiences and school types. A structured questionnaire with 15 items was distributed both online and offline to gather data on teachers’ knowledge, experience, and perceptions of Scratch. The collected data were validated and analyzed using descriptive statistics with SPSS version 25, including frequency and percentage distributions. The results revealed that 68% of teachers had never attended Scratch training, 20% had developed Scratch-based learning media, and 67% faced difficulties in creating their own media. However, 97% supported the integration of Scratch into the teaching process, and 95% expressed the need for Scratch as an alternative medium to enhance computational thinking and digital literacy. These findings highlight the importance of targeted training programs and institutional support to enhance teachers’ competence in using Scratch effectively in elementary classrooms.